STRATEGIC ANALYSIS OF TESCO SUPERMARKET - Raja Sharah Fatricia (Jurnal Manajemen Terapan dan Keuangan, 2017)
Having heavily invested in the entrance of Fresh & Easy to the US market, management is facing several questions and wonders what the best strategy will be in the near future. The central question examined and answered in this report is therefore; Which strategy should Tesco Fresh & Easy pursue in order to make a gross profit of 100 million in the US in 2013?. After a thorough internal and external analysis, a SWOT analysis is made, of which three relevant strategic options are derived. These possible strategic options are evaluated using several evaluation criteria and subsequently, one strategic option is suggested to be the best strategic option for Fresh & Easy in their current situation. This report concludes with It is suggested that implementing a customer intimacy and local focus is the best strategy for Fresh & Easy. Although it does not immediately realize the company’s initial objectives, it will help Fresh & Easy to survive in the US market and to be more profitable (in order to keep existing). Fresh & Easy should target the rapidly growing and ethically diverse population and focus on the ‘True friends’. It must position itself as the neighborhood supermarket that is responsible, interested, familiar, listens, interacts and offers the products that these customers wants. This report concludes with some implementation suggestions and broad financial forecasts. When implementing this customer intimacy and local strategy the right way, Fresh & Easy will most likely make profit after the approximately two years.